Pendampingan dan Pelatihan Peningkatan Pengetahuan Tata Kelola Administrasi Keuangan - Santi, Rina Candra Noor; Yulianton, Heribertus; Eniyati, Sri; Sutanto, Felix Andreas; Hadiono, Kristophorus (Perkumpulan Kualitama Edukatika Indonesia, 2023)
This growing technology, lots of applications and notifications that are growing every year. With the existence of increasingly developing technology, there are many problems that exist. The problem that often occurs in the finance department is that when recording financial data, it often experiences delays in calculating deficiencies, excesses or the percentage profit obtained. Likewise, when searching for data, it often encounters problems if there are some data that need to be revised. This is what often happens to savings and loans at Dawis Melati, because the records are still manual.